Essentials of world regional geography - Bradshaw, Michael J. |q(Michael John) 1935- (Essentials of, 2008)
Essentials of world regional geography; Europe; Russia and neighboring countries; East Asia; Southeast Asia, Australia, and Oceania; South Asia; Northern Africa and Southwestern Asia; Africa South of the Sahara; Latin America; North America.